2016
DOI: 10.1159/000438613
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Profiling of Triple-Negative Breast Carcinomas Tissue Glycoproteome by Sequential Purification of Glycoproteins and Stable Isotope Labeling

Abstract: Background: Women with triple negative breast cancers (TNBCs) have a poor prognosis due to lack of suitable targeted therapies. Changes in the protein glycosylation are increasingly being recognized as an important modification associated with cancer etiology. Methods: In an attempt to identify TNBC biomarkers with greater diagnostic and prognostic capabilities, hydrazide- based chemistry method combined with LC-MS/MS were used to purify and identify N-linked glycopeptides or glycoproteins of tissues from TNBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…identified that the CCR7 splicing imbalance was associated with clinical outcomes. Therefore, a close examination of CCR7 alternative splicing in breast cancer should be performed to disclose the associations of this key post-transcriptional regulation with patient survival [18]. …”
Section: Discussionmentioning
confidence: 99%
“…identified that the CCR7 splicing imbalance was associated with clinical outcomes. Therefore, a close examination of CCR7 alternative splicing in breast cancer should be performed to disclose the associations of this key post-transcriptional regulation with patient survival [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Chen et al, through hydrazide-based chemistry method combined with liquid chromatography tandem-mass spectrometry (LC-MS/MS), identified 72 unique N-linked glycoproteins that were significantly regulated in triple negative breast cancers, among which is LGALS3BP. LGALS3BP is a highly-glycosylated galectin-3 binding protein whose bio-physiological activity is not yet well defined, but recent findings point to a possible involvement with cancer growth and progression [225]. …”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 99%
“…Glycosylation was with the hydrolytic products (i.e., glucose and fructose) since sucrose was a non-reducing sugar; indeed, glucose was detected after L2/L3 insonation (with levels of 0, 0, 2.1±0.2, and 10.6±5.7 μg/ml in control, L1-, L2-, and L3-treated samples, respectively). Glycosylation impacted on the function of a protein [12, 13]. Ultrasound can accelerate the hydrolysis of sucrose, and enhance the protein-sugar reactions to form conjugates via free –OH, –COOH or –NH 2 in the protein [14, 15].…”
Section: Resultsmentioning
confidence: 99%